Contribution of cancer leagues to the promotion and organisation of cancer screening programmes - Ritchie, David (Journal of Health Inequalities, 2017)
The European Union Council Recommendation of 2003 outlines the key principles of best practice in the systematic screening and early detection of cancer, calling on EU member states to develop and implement organised, population-based screening programmes for breast, cervical and colorectal cancer. This short communication outlines, with three practical examples, the variety of ways in which cancer leagues are supporting the development, management, and quality improvement of organised cancer screening in the wider European region. The contribution of cancer leagues is a key sustaining factor for the full and equitable implementation of organised cancer screening programmes, in compliance with the EU guidelines for quality assurance in cancer screening. Both the Portuguese League against Cancer and the Icelandic Cancer Society manage and implement the national breast cancer programmes in their respective countries. The Icelandic Cancer Society also manages the cervical cancer screening programme in parallel. The Israel Cancer Association initiated, and funded for over two decades, the national mammography screening programme in Israel, which has been instrumental in eliminating the disparity in screening participation between Jewish and Arab ethnic women. As initiators, programme managers, and disseminators of information to professionals and the target groups for screening, cancer leagues perform essential and diverse roles supporting cancer screening programmes to achieve their goals. ECL intends to harness this activity in the coming years by deepening the collaboration between cancer leagues on this issue, thereby acting on the ECL’s strategic goal to “encourage access to cancer screening.”